Media Social - Instagram Usage And Performance Benefit (Case Study On Housewives Online Seller In Indonesia) - Marisya Mahdia Khoirina; Nova Ridho Sisprasodjo (LPPM of NAROTAMA UNIVERSITY, 2018)
Purpose: The purposes of this study are to determine the effect of compatibility, cost effectiveness, trust, and interactivity on the use and the effect of media social (instagram) on the non-financial performance and financial performance. Design/methodology/approach: This is a quantitative study approach. Statistical analyses were based on the data collected, through online and offline survey questionnaire from 265 housewife online seller in Indonesia with the accidental sampling technique. Structural Equation Modelling (SEM) was used to test the hypotheses. Findings: The findings in this research are: (1) compatibility has no impact on the use of Instagram, (2) cost effectiveness has a strong positive impact on the use of Instagram,(3) trust has a npositive impact on the use of Instagram, (4) interactivity has a strong positive impact on the use of Instagram, (5) the use of Instagram has a strong positive impact on non-financial performance, and (6) the use of Instagram has no impact on financial performance Research limitations/implications: This study is limited in selection of samples. The samples only covered on online seller from housewife in Indonesia which limits generalizability of the findings. Practical implications: Instagram is expected to always be able to innovate and update features with better quality so that it can still be used by online sellers from housewife. And for online sellers from house wife in Surabaya are expected consider various factors in the selection of online sales media, especially Instagram. This is very important because it will affect only the non-financial performance. The selection of the right sales media will have a positive impact on developing the business world to become bigger. Paper type: Research paper